2018
DOI: 10.1097/eja.0000000000000827
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of closed-loop-assisted intra-operative goal-directed fluid therapy during major abdominal surgery

Abstract: NCT02978430.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 26 publications
0
25
1
Order By: Relevance
“…We have demonstrated that implementation of this "computer system" resulted in less intraoperative time spent in a preload-dependent state (stroke volume variation > 13%) compared to a manually applied protocol, using both minimally invasive and noninvasive technologies [43,44]. Implementation of these systems at the patient's bedside has also been associated with better patient outcomes compared to routine care [45]. The software for this technology has now been implemented into the EV1000 monitoring device as a real-time clinical decision support system and is widely available for clinical use [46].…”
Section: Yesmentioning
confidence: 97%
“…We have demonstrated that implementation of this "computer system" resulted in less intraoperative time spent in a preload-dependent state (stroke volume variation > 13%) compared to a manually applied protocol, using both minimally invasive and noninvasive technologies [43,44]. Implementation of these systems at the patient's bedside has also been associated with better patient outcomes compared to routine care [45]. The software for this technology has now been implemented into the EV1000 monitoring device as a real-time clinical decision support system and is widely available for clinical use [46].…”
Section: Yesmentioning
confidence: 97%
“…There are no guidelines concerning perioperative fluid therapy for patients with end-stage renal failure (ESRF) [1]. Nearly all the studies of perioperative fluid therapy excluded patients with ESRF because of their physical condition [1][2][3][4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Although it only takes into account the fluid component of GDHT (i.e. preload optimization), it increases protocol compliance and was associated with improved outcome when compared to fluid therapy based on a static parameters of fluid responsiveness[78]. In addition, when compared to manual goal-directed fluid therapy, this system maintains patients in a preload independent state for a longer period of time[81,82].…”
mentioning
confidence: 99%